The Small Protein YmoA Controls the Csr System and Adjusts Expression of Virulence-Relevant Traits of Yersinia pseudotuberculosis - Böhme, Katja; Heroven, Ann Kathrin; Lobedann, Stephanie; Guo, Yuzhu; Stolle, Anne-Sophie; Dersch, Petra (Frontiers in Microbiology, 2021)
Virulence gene expression of Yersinia pseudotuberculosis changes during the different stages of infection and this is tightly controlled by environmental cues. In this study, we show that the small protein YmoA, a member of the Hha family, is part of this process. It controls temperature- and nutrient-dependent early and later stage virulence genes in an opposing manner and co-regulates bacterial stress responses and metabolic functions. Our analysis further revealed that YmoA exerts this function by modulating the global post-transcriptional regulatory Csr system. YmoA pre¬dominantly enhances the stability of the regulatory RNA CsrC. This involves a stabilizing stem-loop structure within the 5’-region of CsrC. YmoA-mediated CsrC stabilization depends on H-NS, but not on the RNA chaperone Hfq. YmoA-promoted reprogramming of the Csr system has severe consequences for the cell: we found that a mutant deficient of ymoA is strongly reduced in its ability to enter host cells and to disseminate to the Peyer’s patches, mesenteric lymph nodes, liver and spleen in mice. We propose a model in which YmoA controls transition from the initial colonization phase in the intestine towards the host defense phase important for the long-term establishment of the infection in underlying tissues.